Subtract: [tex]\frac{6}{2x^2+8x} -\frac{x}{4x^2+12-16} =\frac{6}{2x(x+4)} -\frac{x}{4(x+4)(x-1)} =\frac{6*2(x-1)}{2x(x+4)*2(x-1)} -\frac{x*x

Question

Subtract: \frac{6}{2x^2+8x} -\frac{x}{4x^2+12-16} =\frac{6}{2x(x+4)} -\frac{x}{4(x+4)(x-1)} =\frac{6*2(x-1)}{2x(x+4)*2(x-1)} -\frac{x*x}{4(x+4)(x-1)*x}

A:\frac{-2x^2+12x-12}{2(x+4)(x-1)}
B:\frac{-x^2+6x-6}{2(x+4)(x-1)}
C:\frac{-2x^2+12x-12}{4(x+4)(x-1)}
D:\frac{-x^2+12x-12}{4x(x+4)(x-1)}

in progress 0
Tài Đức 2 days 2021-07-21T23:29:26+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-21T23:30:45+00:00

    Step-by-step explanation:

    I think D

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )